2021
DOI: 10.20964/2021.10.56
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Species in Lycoris spp. from stigmatic exudate using electrochemical fingerprints

Abstract: The use of electrochemical fingerprints for plant identification is an emerging application in biosensors. In this work, stigmatic exudate was collected from plants and the electrochemical fingerprints were taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…It shows the difference of kinship between different plants by the difference of electrochemically active substances in plant tissues. Our previous works have successfully confirmed the feasibility of this technique in phylogenetic investigations [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The electrochemical active components of plants, such as flavonoids and phenols, fluctuate according to species’ distance from each other.…”
Section: Introductionmentioning
confidence: 74%
“…It shows the difference of kinship between different plants by the difference of electrochemically active substances in plant tissues. Our previous works have successfully confirmed the feasibility of this technique in phylogenetic investigations [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. The electrochemical active components of plants, such as flavonoids and phenols, fluctuate according to species’ distance from each other.…”
Section: Introductionmentioning
confidence: 74%
“…The choice of electrodes plays a very important role in electrochemical sensing. We have made a series of attempts at electrode modification [ 8 , 9 , 10 , 11 , 12 ]. The results indicated that the electrode modification of nanomaterials inevitably produces some disturbing signals.…”
Section: Resultsmentioning
confidence: 99%
“…The use of electrochemical fingerprinting of plant tissues for species identification is an identification method that has emerged in recent years [ 7 ]. The principle of this technique is the diversity of electrochemically active components in different plant tissues [ 8 , 9 , 10 , 11 , 12 ]. This variation reflects, to some extent, genetic differences between species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these species show similar electrochemical oxidation trend, with an obvious electrochemical oxidation peak near 0.4 V. This similarity in electrochemical behavior is common among plants of the same genus. This is because species within the genus have relatively similar genes, and therefore have a high degree of similarity in the species of electrochemically active molecules in tissues ( Ye et al., 2021 ). However, beyond the obvious large oxidation peak of about 0.4 V, different species showed different electrochemical behaviors.…”
Section: Resultsmentioning
confidence: 99%